ПЕРЕВОД КАК СРЕДСТВО МЕЖКУЛЬТУРНОЙ КОММУНИКАЦИИ В СОВРЕМЕННОМ МИРЕ - Орехин-Рыжина Вита Александровна; Магфурова Зубайда (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
This article explores the role of translation as a means of intercultural communication in the modern world, where the importance of communication between people of different languages ​​and cultures is invaluable. Various aspects of translation are discussed, including the influence of interference on the textual transmission process and the adaptation of cultural specifics. Particular attention is paid to the role of the translator as a mediator of cultures, as well as the ethical and aesthetic aspects of translation in the context of intercultural interaction.